PATIENTS’ PERCEPTION TOWARDS GENERAL AND PELVIC EXAMINATION BY MALE MEDICAL STUDENTS - Thirunavuk Arasoo, Valliammai Jayanthi (UNG, 2026)
Male medical students globally have difficulty in obtaining consent to perform pelvic examinations. We sought to identify independent factors influencing women consenting to male medical students performing general and pelvic examinations under supervision. This cross-sectional study was conducted at a tertiary hospital and a public health care centre in Johor Bahru, Malaysia where 369 women above 18 years old who have had sexual intercourse and no prior hysterectomy were recruited. A validated self-administered bilingual questionnaire was used to collect data on factors that influence them consenting to male medical students examining them and performing pelvic examination when indicated. The respondents were mostly below 30 years old (52.9%), Malays (73.4%), and Muslims (75.3%). The consent rates for general and pelvic examination were 27.4% and 18.9%, respectively. Being a Muslim, having an occupation, and being introduced by a male medical specialist increased women's likelihood of consenting to a general examination. However, a history of being examined by male students decreased the likelihood by 64%. Believing that male doctors should have the skills to treat patients in women's health was the only independent factor that increased the likelihood for women to consent for pelvic examinations to be conducted by male medical students. Believing that male doctors should be skilled in treating women positively influences the decision to consent. Explaining earnestly to women how they aid in developing the skills of future doctors should be prioritised.